2019
DOI: 10.1038/s41598-019-41738-5
|View full text |Cite
|
Sign up to set email alerts
|

The potential probiotic Lactobacillus rhamnosus CNCM I-3690 strain protects the intestinal barrier by stimulating both mucus production and cytoprotective response

Abstract: The gut barrier plays an important role in human health. When barrier function is impaired, altered permeability and barrier dysfunction can occur, leading to inflammatory bowel diseases, irritable bowel syndrome or obesity. Several bacteria, including pathogens and commensals, have been found to directly or indirectly modulate intestinal barrier function. The use of probiotic strains could be an important landmark in the management of gut dysfunction with a clear impact on the general population. Previously, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 79 publications
6
94
0
Order By: Relevance
“…L. paracasei CNCM I-3689 decreased the translocation and dissemination of Listeria monocytogenes 15 , induced the clearance of vancomycin-resistant enterococci 16 and promoted the resilience of some members of the microbiota following exposure to an antibiotic challenge in mice 16 . In addition, L. rhamnosus CNCM I-3690 counteracted the increase in intestinal permeability induced by mild inflammation 18,19 , and prevented blooms of the pathobiont Bilophila wadsworthia and related deleterious host metabolic effects in mice fed with a high-fat diet 17 . Moreover, L. paracasei CNCM I-1518, modulated the activity of Faecalibacterium prausnitzii in an in vitro gut model 20 .…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…L. paracasei CNCM I-3689 decreased the translocation and dissemination of Listeria monocytogenes 15 , induced the clearance of vancomycin-resistant enterococci 16 and promoted the resilience of some members of the microbiota following exposure to an antibiotic challenge in mice 16 . In addition, L. rhamnosus CNCM I-3690 counteracted the increase in intestinal permeability induced by mild inflammation 18,19 , and prevented blooms of the pathobiont Bilophila wadsworthia and related deleterious host metabolic effects in mice fed with a high-fat diet 17 . Moreover, L. paracasei CNCM I-1518, modulated the activity of Faecalibacterium prausnitzii in an in vitro gut model 20 .…”
mentioning
confidence: 97%
“…A product containing yogurt and three probiotic candidate strains, Lactobacillus paracasei CNCM I-3689, Lactobacillus rhamnosus CNCM I-3690 and Lactobacillus paracasei CNCM I-1518, combined in a fermented milk matrix, was designed. Several preclinical studies have suggested that these three strains could modulate the gut barrier and/or the gut microbiota [15][16][17][18][19] . L. paracasei CNCM I-3689 decreased the translocation and dissemination of Listeria monocytogenes 15 , induced the clearance of vancomycin-resistant enterococci 16 and promoted the resilience of some members of the microbiota following exposure to an antibiotic challenge in mice 16 .…”
mentioning
confidence: 99%
“…Finally, it is important to call attention to the ability of L. rhamnosus to form a biofilm. It is well documented that the ability to adhere to mammalian tissues constitutes a crucial feature that potential probiotic bacteria must exhibit if they are to adapt to the gastrointestinal tract [64]. The strain of L. rhamnosus isolated here (as described later on), however, showed no resistance to acid or bile salts.…”
Section: Enzymatic Tests and Biofilm Formationmentioning
confidence: 71%
“…The ability of some microorganisms to form biofilms has generated much debate about the potential threat that these microorganisms, in this case bacteria, may pose to human health. In fact, while microbial adherence, in particular adherence to plastic or human tissues, is widely considered a threat for human health in terms of it providing a route to pathogenic contamination (for example, via indwelling medical devices such as urinary catheters), it is also seen as a highly positive trait, especially for probiotic microorganisms able to adhere to and persist in the gastro-intestinal tract [64]. Of the bacteria isolated in this work, the following showed strong biofilm formation ability: Eight strains of B. amyloliquefaciens, four strains of B. agri, one strain of B. subtilis, one strain of Br.…”
Section: Enzymatic Tests and Biofilm Formationmentioning
confidence: 99%
“…A number of bacterial species have been shown to modulate mucin secretion by goblet cells. For example, commensal Ruminococcus gnavus and Lactobacillus rhamnosus stimulate the production of mucins, while pathogenic microbes including adherent and invasive Escherichia coli promote a less effective mucus barrier . In a recent study, Amuc_1100, a membrane protein from commensal Akkermansia muciniphila , was shown to interact with the PRR Toll‐like receptor 2 (TLR2) to increase intestinal barrier function, namely mucus thickness and tight junction protein (TJP) expression …”
Section: Microbiota–iec Crosstalkmentioning
confidence: 99%